Work Environment, Compensation, Work Motivation, Leadership Style, and Employee Work Productivity: Evidence from PT Bumi Menara Internusa - Andika Saputra; Fahriyan Canda; Aditya Putra Mahendra; Febrianty Febrianty; Reza Rahardian Pratama (IJBLE Scientific Publications Community Inc., 2026)
This study examines the effects of work environment and compensation on employee work productivity, while considering the roles of work motivation and leadership style in a labor-intensive marine product processing company, PT Bumi Menara Internusa. The study applied a quantitative explanatory design and collected questionnaire data from 81 employees. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0. The measurement model showed acceptable indicator reliability, with standardized outer loadings ranging from 0.789 to 0.921 and construct reliability values exceeding the recommended threshold. The structural model explained 80.5% of the variance in leadership style and 80.0% of the variance in employee work productivity. Work motivation had a positive and significant effect on work productivity (β = 0.386, t = 2.335, p = 0.020). In contrast, the direct effects of work environment (β = 0.310, p = 0.141), compensation (β = 0.180, p = 0.248), and leadership style (β = -0.097, p = 0.627) on work productivity were not significant. Work environment positively influenced leadership style (β = 0.562, p < 0.001), whereas compensation had a negative significant effect on leadership style (β = -0.364, p = 0.003). Interaction effects involving work motivation were not significant. These findings indicate that productivity improvement in this organizational context is more strongly associated with employees’ internal motivational drive than with direct improvements in work environment, compensation, or leadership style alone. The study contributes to human resource management literature by showing the differentiated roles of job resources, compensation practices, motivation, and leadership in explaining employee productivity in an Indonesian industrial context.